Corrosion of Low-Alloy Steel in Ethanolamine Steam Generator Chemistry—The Effect of Temperature and Flow Rate - Iva Betova; Martin Bojinov; Vasil Karastoyanov (Molecules)
The corrosion of low-alloy steel in ethanolamine solution, simulating steam generator chemistry, is studied by in situ chronopotentiometry and electrochemical impedance spectroscopy combined with ex situ analysis of the obtained oxide films and model calculations. Hydrodynamic calculations of the proposed setup to study flow-assisted corrosion demonstrate that turbulent conditions are achieved. Quantum chemical calculations indicate the adsorption orientation of ethanolamine on the oxide surface. Interpretation of impedance spectra with a kinetic approach based on the mixed-conduction model enabled estimating the rate constants of oxidation at the alloy–oxide interface, as well as charge transfer and ionic transport resistances of the corrosion process. In turbulent conditions, the dissolution of Fe oxide and ejection of Fe cations are enhanced, leading to Cr enrichment in the oxide and alteration of its electronic and electrochemical properties that influence the corrosion rate.